ANALISIS PERAN ISTRI DALAM MEMBANTU PEREKONOMIAN KELUARGA DI KOTA TIMIKA - Fitriani Rantela'bi'; Tharsisius Pabendon (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the role of the wife in helping the family economy in Timika City. The data collected in this study is qualitative data using a questionnaire. Data analysis in this study was carried out using Chi-Square K-Sample analysis. From the results of the analysis that has been carried out, it is found that the wife plays a significant role in helping the family economy in Timika City because if the wife also works, the family income increases